Mogroside IIIE Attenuates LPS‐Induced Acute Lung Injury in Mice Partly Through Regulation of the TLR4/MAPK/NF‐κB Axis via AMPK Activation. (17th May 2017) - Tao, Lijun; Cao, Fengyan; Xu, Gonghao; Xie, Haifeng; Zhang, Mian; Zhang, Chaofeng
Abstract : Acute lung injury (ALI) often leads to high mortality, and there is as yet no effective drug treatment. The present study aimed to investigate protective effects of mogroside IIIE (MGIIIE, a cucurbitane‐type triterpenoid from Siraitia grosvenorii Fruits) in experimental ALI and its underlying mechanism. MGIIIE (1, 10 0r 20 mg/kg) was orally administered for 1 h before a single intratracheal administration of lipopolysaccharide (LPS, 5 mg/kg). MGIIIE treatment dose‐dependently suppressed pulmonary oedema, pro‐inflammatory mediators (IL‐1β, IL‐6, TNF‐α and HMGB1) release and higher MPO activity in lung tissues induced by LPS challenge. Molecular researches showed that mogroside IIIE (20 mg/kg) not only increased the phosphorylation of adenosine 5′‐monophosphate‐activated protein kinase (AMPK) but suppressed the over‐expression of toll‐like receptor 4 (TLR4) and myeloid differentiation factor 88 (MyD88). In addition, MGIIIE also inhibited the activation of MAPKs and nuclear factor κB (NF‐κB) signalling in lung tissues from LPS‐challenged mice. Similar antiinflammatory effects of MGIIIE were obtained in LPS‐treated macrophages. Compound C (a pharmacological AMPK inhibitor) obviously reversed the antiinflammatory effect of MGIIIE in LPS‐induced ALI mice. Taken together, AMPK activation plays a crucial role in the antiinflammatory effects of MGIIIE in LPS‐induced ALI by down‐regulating TLR4/MAPK/NF‐κB signalling pathways. Copyright © 2017 John Wiley & Sons, Ltd.